Bacteriological Profile and Antibiotic Sensitivity Patterns in Children with Urinary Tract Infection: A Cross-Sectional Study in the Northern Part of Bangladesh (Global Journal of Medical Research, 2023)
Purpose Urinary tract infection UTI is a prevalent infection in children Over the years the sensitivity and antimicrobial resistance patterns against uropathogens causing this infection have continuously changed Pediatricians need updated knowledge of the antimicrobial sensitivity and resistance patterns of common uropathogens to provide appropriate treatment This study aimed to determine the spectrum of causative uropathogens antimicrobial sensitivity and resistance patterns in pediatric patients Methods A single-center cross-sectional study was conducted from February 2021 to January 2022 at the tertiary care hospital in Rangpur Bangladesh s northernmost division A total of 200 children aged 0 months to 12 years with clinically suspected UTIs were enrolled in the study Researchers reviewed the study participants medical records and sent the urine sample for routine and microscopic examination and culture sensitivity testing
Keywords: urinary tract infection children bacteriological profile antibiotic sensitivity